Analysis of Contextualization in Ramiro Pinilla’s Detective Novel: the Post Civil War Getxo - Feijoo Morote, Javier (Pasavento. Revista de Estudios Hispánicos, 2016)
The narrative work of Ramiro Pinilla has recently been acknowledged with an increasing appreciation by academic criticism and public in general. His crime novel series, consisting of Sólo un muerto más (2009), El cementerio vacío (2013) and Cadáveres en la playa (2014) provide the proper structures to his aim to participate in the building of “critical memory novel”: the search for truth and knowledge as the only mean to build a common future and to defeat oblivion. The present article analyses the effects of the choice of spatiotemporal locations to recreate a time lost in the Spanish collective memory and to transmit the echoes of a meditated intransigence and of an unresolved contradiction between the past and the present of Spain.